Phononic crystal plate with hollow pillars connected by thin bars. (7th December 2016) - Jin, Yabin; Pennec, Yan; Pan, Yongdong; Djafari-Rouhani, Bahram
Abstract: A new type of phononic crystal plate consisting of hollow pillars on a bar-connected plate is proposed. With respect to usual pillar based phononic crystal plates, the Bragg band gap can be tuned to be much wider and extended to a sub-wavelength region, and the low frequency gap can be moved to an extremely low frequency range. Such a structure can generate quadrapolar, hexapolar and octopolar whispering-gallery modes (WGMs) inside the band gaps with very high confinement and quality factors. By filling the hollow pillars with a liquid, these WGMs, together with additional localized compressional and solid–liquid coupling modes, can be tuned either by varying the inner radius of the pillars or controlling the height of the liquid. We discuss some possible functionalities of these phononic crystals for the purpose of sensing the acoustic properties of liquids, multiplexer and wireless communication.